Single-neuron diversity generated by Protocadherin-β cluster in mouse central and peripheral nervous systems - Hirano, Keizo; Kaneko, Ryosuke; Izawa, Takeshi; Kawaguchi, Masahumi; Kitsukawa, Takashi; Yagi, Takeshi (Frontiers in Molecular Neuroscience, 2012)
The generation of complex neural circuits depends on the correct wiring of neurons with diverse individual characteristics. To understand the complexity of the nervous system, the molecular mechanisms for specifying the identity and diversity of individual neurons must be elucidated. The clustered protocadherins (Pcdh) in mammals consist of approximately 50 Pcdh genes (Pcdh-α, Pcdh-β, and Pcdh-γ) that encode cadherin-family cell surface adhesion proteins. Individual neurons express a random combination of Pcdh-α and Pcdh-γ, whereas the expression patterns for the Pcdh-β genes, 22 one-exon genes in mouse, are not fully understood. Here we show that the Pcdh-β genes are expressed in a 3’-polyadenylated form in mouse brain. In situ hybridization using a pan-Pcdh-β probe against a conserved Pcdh-β sequence showed widespread labeling in the brain, with prominent signals in the olfactory bulb, hippocampus, and cerebellum. In situ hybridization with specific probes for individual Pcdh-β genes showed their expression to be scattered in Purkinje cells from P10 to P150. The scattered expression patterns were confirmed by performing a newly developed single-cell 3’-RACE analysis of Purkinje cells, which clearly demonstrated that the Pcdh-β genes are expressed monoallelically and combinatorially in individual Purkinje cells. Scattered expression patterns of individual Pcdh-β genes were also observed in pyramidal neurons in the hippocampus and cerebral cortex, neurons in the trigeminal and dorsal root ganglion, GABAergic interneurons, and cholinergic neurons. Our results extend previous observations of diversity at the single-neuron level generated by Pcdh expression and suggest that the Pcdh-β cluster genes contribute to specifying the identity and diversity of individual neurons.